2000
DOI: 10.1002/(sici)1521-3765(20000317)6:6<949::aid-chem949>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of 2-Methyl Cyclohexane Carboxylic Acids by Heterogeneous Catalysis: Mechanistic Aspects

Abstract: The catalytic hydrogenation of (S)-alkyl-N-(2-methylbenzoyl)pyroglutamates was studied over supported rhodium and ruthenium catalysts at room temperature and a pressure of 5 MPa. The reaction was diastereoselective with the predominant formation of (1S,2R)-2-methylcyclohexane carboxylic acid with a diastereomeric excess (de) of up to 96%. The most stable conformation was determined by means of a combination of modelling calculations, NMR spectroscopy and X-ray structural determination. In this conformation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…This stringent requirement is also present in other technological sectors such as fragrances, flavours and agrochemicals. There are a number of different approaches which have been used to create heterogeneous chiral catalysts including: immobilising chiral transition metal complexes at surfaces [2]; attaching chiral auxiliaries to the reactant to induce an asymmetry in the surface reaction [3]; creating intrinsically chiral surfaces in which asymmetric configurations of the reactive surface are displayed [4]; and, finally, adsorbing chiral molecules at achiral solid surfaces to induce asymmetry [5]. The work discussed here directly impinges on the last case, where there are several successful examples of introducing enantioselectivity to heterogeneous reactions by modifying surfaces via the adsorption of chiral organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This stringent requirement is also present in other technological sectors such as fragrances, flavours and agrochemicals. There are a number of different approaches which have been used to create heterogeneous chiral catalysts including: immobilising chiral transition metal complexes at surfaces [2]; attaching chiral auxiliaries to the reactant to induce an asymmetry in the surface reaction [3]; creating intrinsically chiral surfaces in which asymmetric configurations of the reactive surface are displayed [4]; and, finally, adsorbing chiral molecules at achiral solid surfaces to induce asymmetry [5]. The work discussed here directly impinges on the last case, where there are several successful examples of introducing enantioselectivity to heterogeneous reactions by modifying surfaces via the adsorption of chiral organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Di-tert-butyl (2S,4E)-4-[(dimethylamino)methylidene]-5-oxopyrrolidine-1,2-dicarboxylate (4) was prepared from 1 following the literature procedures [5c, 10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we report the result of this study -a simple parallel solution-phase pyroglutamic acid (1) following the literature procedures [5c, 10,11]. Thus, acid-catalysed esterification of (S)-pyroglutamic acid (1) with tert-butyl acetate gave tert-butyl pyroglutamate (2) [10], which was N-acylated with Boc 2 O in acetonitrile in the presence of catalytic amounts of 4-dimethylaminopyridine (DMAP) to afford di-tert-butyl (2S)-5-oxopyrrolidine-1,2-dicarboxylate (3) [11]. Finally, heating of 3 with one equivalent of tert-butoxy-bis(dimethylamino)methane (Bredereck s reagent, TBDMAM) furnished di-tert-butyl (2S,4E)-4-[(dimethylamino)-methylidene]-5-oxopyrrolidine-1, 2-dicarboxylate (4) in 70 % yield over three steps [5c] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting substrate possesses two most stable conformations, as calculated by molecular modeling with a very small energy difference (1 kJ mol −1 ) and a very large interconversion barrier (>1000 kJ mol −1 ), which indicated that there is no possible interconversion between these two conformers [112]. X-ray structural analysis of the substrate indicated that only one conformer was effectively present.…”
Section: Diastereoselective Hydrogenation Of Aromatic Ringsmentioning
confidence: 95%